1999
DOI: 10.1073/pnas.96.6.3320
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome evidence for ancient human histories

Abstract: Diverse African and non-African samples of the X-linked PDHA1 (pyruvate dehydrogenase E1 ␣ subunit) locus revealed a fixed DNA sequence difference between the two sample groups. The age of onset of population subdivision appears to be about 200 thousand years ago. This predates the earliest modern human fossils, suggesting the transformation to modern humans occurred in a subdivided population. The base of the PDHA1 gene tree is relatively ancient, with an estimated age of 1.86 million years, a late Pliocene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
110
4
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(128 citation statements)
references
References 40 publications
13
110
4
1
Order By: Relevance
“…These estimates are significantly younger than those estimated from the data at 22q11.2 (1.29 MY), 1q24 (1.47 MY), PDHA1 (1.86 MY), and MC1R (1.52 MY) (Harris and Hey 1999;Zhao et al 2000;Makova et al 2001;Yu et al 2001). However, they are comparable to other estimates based on the data from the b-globin gene (750,000), Xq13.3 (535,000), and Xq21.31 (710,000) (Harding et al 1997;Kaessmann et al 1999;Yu et al 2002b).…”
Section: à4contrasting
confidence: 46%
“…These estimates are significantly younger than those estimated from the data at 22q11.2 (1.29 MY), 1q24 (1.47 MY), PDHA1 (1.86 MY), and MC1R (1.52 MY) (Harris and Hey 1999;Zhao et al 2000;Makova et al 2001;Yu et al 2001). However, they are comparable to other estimates based on the data from the b-globin gene (750,000), Xq13.3 (535,000), and Xq21.31 (710,000) (Harding et al 1997;Kaessmann et al 1999;Yu et al 2002b).…”
Section: à4contrasting
confidence: 46%
“…This observation, together with the deeper TMRCA of the MEFV minor clade, suggests that haplogroup 3 ( Figures 1 and 2) is accounted for by ancient population structure in the African continent, in line with the idea that African populations have been more subdivided compared with non-African ones. 31,[37][38][39][40][41][42] We used two different methods to infer the TMRCA of the two major MEFV haplotype clades: estimates vary slightly depending on the method used, yielding a rough estimation of B1.70 MY with wide confidence intervals. Estimates of TMRCAs for neutrally evolving autosomal human loci range between 0.8 and 1.5 MY; 42 therefore, the TMRCA we estimated for MEFV, although not exceptional, is deeper than for most neutrally evolving loci.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of natural selection on patterns of nucleotide variation tend to be localized to small chromosomal regions (i.e., sites linked to those subject to selection) due to the dissociating effect of recombination. Given that Xp21.1 maps to a region of moderately high recombination ‫9.1ف(‬ cM/Mb; http://genome.ucsc.edu) and (Cann et al 1987;Harpending et al 1998;Harris and Hey 1999; isms is expected, which is not observed at the Xp21.1 locus trio (e.g., Tajima's D ϭ Ϫ0.378). Additionally, Taka Takahata et al 2001;Excoffier 2002).…”
Section: ϫ4mentioning
confidence: 99%
“…Additional coalescent simulations of a 100-fold population reduction occurring ‫001ف‬ KYA yield E(l b ) ϭ 9.70. However, this alternative model is unlikely to be viable for the human population since the effects of a reduced N e (in the absence of population structure) are expected to be visible throughout the entire genome, and no consistent evidence for an ancient African bottleneck has been detected in surveys of nucleotide variation at other loci (Harding et al 1997;Harris and Hey 1999;Ingman et al 2000;Wall and Przeworski 2000;Zhao et al 2000;Alonso and Armour 2001;Frisse et al 2001;Harding and McVean 2004). The effects of natural selection on patterns of nucleotide variation tend to be localized to small chromosomal regions (i.e., sites linked to those subject to selection) due to the dissociating effect of recombination.…”
Section: ϫ4mentioning
confidence: 99%
See 1 more Smart Citation